2007
DOI: 10.1021/ma070977p
|View full text |Cite
|
Sign up to set email alerts
|

Micellar Morphologies of Poly(ε-caprolactone)-b-poly(ethylene oxide) Block Copolymers in Water with a Crystalline Core

Abstract: The self-assembly of poly(ε-caprolactone)-b-poly(ethylene oxide) block copolymers (PCL n PEO44 and PCL n PEO113) with narrow polydispersity in aqueous medium was studied using transmission electron microscopy. In this system, the formed micelles are composed of a crystalline PCL core and a soluble PEO corona. We demonstrated that the PCL-b-PEO block copolymers can form micelles with abundant morphologies, depending on the lengths of the blocks and composition. It is observed that for PCL n PEO44 the micellar m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
241
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(249 citation statements)
references
References 51 publications
8
241
0
Order By: Relevance
“…[4][5][6] In an aqueous system, the hydrophobic block aggregates to form a micellar core and the hydrophilic block constitutes the outer shell. [4][5][6] Fluorescence spectra based on selective emission of pyrene in hydrophobic phase against aqueous phase have been used with great success for the measurement of CMC. [13,18,19] The CMC is an effective parameter of micellar stability, and a low critical value is desired for stable micelles.…”
Section: Self-assembly Behaviours In Watermentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] In an aqueous system, the hydrophobic block aggregates to form a micellar core and the hydrophilic block constitutes the outer shell. [4][5][6] Fluorescence spectra based on selective emission of pyrene in hydrophobic phase against aqueous phase have been used with great success for the measurement of CMC. [13,18,19] The CMC is an effective parameter of micellar stability, and a low critical value is desired for stable micelles.…”
Section: Self-assembly Behaviours In Watermentioning
confidence: 99%
“…The PCLblock-PEG (PCL-b-PEG) copolymer, produced by introducing PEG chains into PCL, can be made into nanoscale micelles in proper solvents. [4][5][6] These drug-loaded nanomicelles can escape from being phagocytized by the reticuloendothelial system, retain for a long time in blood circulation and enrich continuously around the tumour location. [1,2] As a result, they can improve the curative effect of drugs and reduce the toxicity to normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…6,9,10 The first rod-like micelles reported involved poly(ferrocenyldimethylsilane) (PFS) block copolymers. [11][12][13] Other more recent examples of rod-like micelles involve block copolymers with polyethylene (PE), 7,[14][15][16][17][18][19][20] polyacrylonitrile (PAN), 21 polyferrocenyldimethylgermane (PFG), 22 poly(e-caprolactone) (PCL), [23][24][25][26][27][28][29][30] poly(L-lactide) (PLLA), [31][32][33][34][35] and polythiophene, 36,37 as the crystalline core-forming block.…”
Section: Introductionmentioning
confidence: 99%
“…Under many sample preparation conditions and for a variety of different block ratios, multiple morphologies are observed. 28 One study of PCL-b-PEO showed that exposure of spherical micelles in water to high ionic strength led to a morphological transition to lower curvature structures such as rods and lamellae. 26 The authors explained that ionic strength promotes contraction of the PEO chains due to salting-out, and in this way induced the change in morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The overall shape thus depends on the interplay between the interfacial energy of the crystalline block and the solvent, and the stretching within the amorphous block [4]. Thus, the micellar architecture is strongly influenced by the crystallization conditions, such as temperature [9], and composition of the block copolymers [3, 5-By changing composition, solvent, and structure of the crystalline block, spherical [7,[11][12][13], cylindrical [10,14,28], and lamellar micelles have been obtained [1,3,5,15,29]. Recently, Winnik et al reported the possibility to obtain cylindrical micelles with controlled dimensions and architectures of organometallic block copolymers containing the crystallizable polyferrocenyldimethylsilane as one block.…”
Section: Introductionmentioning
confidence: 99%